Analisis Pengetahuan Bahan Pangan Lokal pada Pembelajaran Cookies dan Candies - Larasing Sekarsuci; Ika Wahyu Kusuma Wati; Sri Wahyu Andayani (Wacana Akademika: Majalah Ilmiah Kependidikan, 2025)
This quantitative descriptive study aims to analyze in-depth the level of knowledge of local food ingredients among Culinary Arts students specializing in the Cookies & Candies course in the Vocational Education (PVKK), Universitas Sarjanawiyata Tamansiswa, Academic Year 2023/2024. The urgency of this research lies in the importance of students' understanding of the potential of local resources to support sustainable culinary innovation. The instrument used was a knowledge questionnaire validated by material experts and learning evaluation experts to ensure data accuracy. Data analysis was conducted using descriptive statistical techniques by calculating the average percentage score at each cognitive level. The results revealed that the students' overall level of knowledge of local food ingredients was in the very high category with an average score of 91.30%. Specifically, cognitive indicators covering aspects of knowledge, comprehension, application, analysis, synthesis, and evaluation all showed satisfactory results. This finding confirms that students have a strong level of knowledge in integrating local food ingredients in pastry product processing, which is expected to be the main capital in vocational education.